2012
DOI: 10.12659/msm.883336
|View full text |Cite
|
Sign up to set email alerts
|

Factors that favor the occurrence of cough in patients treated with ramipril – A pharmacoepidemiological study

Abstract: SummaryBackgroundDry cough is a common cause for the discontinuation of ramipril treatment. The aim of this pharmacoepidemiological study was to assess the incidence of ramipril-related cough among the Polish population and to characterize patients at risk of experiencing the adverse effect of cough during ramipril treatment.Material/MethodsThis was a prospective observational study involving 10,380 patients treated with ramipril for a period of no longer than 8 weeks, consisting of 3 visits: baseline, first f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 25 publications
2
14
1
2
Order By: Relevance
“…Therefore, only an indirect comparison with the results of previous studies on ACEI‐induced cough is possible. While we confirmed the association with asthma, the association with COPD was in the opposite direction to that found in the above‐mentioned study . A potential explanation for this could be that ACEI users with COPD who already experience cough as a symptom of COPD might be less likely to attribute cough to ACEIs, and therefore less likely to be switched to ARBs.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Therefore, only an indirect comparison with the results of previous studies on ACEI‐induced cough is possible. While we confirmed the association with asthma, the association with COPD was in the opposite direction to that found in the above‐mentioned study . A potential explanation for this could be that ACEI users with COPD who already experience cough as a symptom of COPD might be less likely to attribute cough to ACEIs, and therefore less likely to be switched to ARBs.…”
Section: Discussioncontrasting
confidence: 58%
“…A study by Wyskida et al . found that asthma and COPD were associated with ACEI‐related cough, with age‐adjusted ORs of 1.60 and 1.70, respectively . Based on validation of the database marker for ACEI intolerance used in our analyses, at least half of the cases of ACEI intolerance in the present study might be considered as having had ACEI‐related cough .…”
Section: Discussionsupporting
confidence: 53%
“…Sex, age, fentanyl, methotrexate, nitrofurantoin, propofol, and drugs for obstructive airway diseases (OADs) – adrenergics (inhalants) and other OADs (inhalants) – were considered as possible risk factors for cough . For angioedema, sex, age, nonsteroidal anti‐inflammatory drugs, contrast agents, and opioids were considered as possible risk factors .…”
Section: Methodsmentioning
confidence: 99%
“… 16 , 17 , 18 , 19 , 20 , 21 In fact, not all ACEI trials included cough as an endpoint, and these studies have been limited by smaller sample sizes and lack of long-term follow-up with a low number of events, which, in turn, has resulted in marked differences in reported incidences. 16 , 17 , 18 , 19 , 20 , 21 Moreover, the incidence of cough varies among individual ACEIs, and only a few ACEIs have real-world clinical practice data to support findings from randomized trials. In this context, perindopril is an ACEI for which extensive evidence from both randomized trials and real-world data are available.…”
Section: Magnitude Of Coughmentioning
confidence: 99%